Early or late enteral feeding for preterm growth-restricted infants? the abnormal doppler enteral prescription trial. (29th September 2015) - Leaf, A; Dorling, J; Kempley, S; McCormick, K; Mannix, P; Brocklehurst, P; Linsell, L
Abstract : Aim: Pregnancies complicated by abnormal antenatal Doppler blood flow often result in the preterm delivery of a growth restricted baby. These babies have a high risk of milk intolerance and necrotising enterocolitis (NEC), and introduction of milk feeds is frequently delayed. The authors' aim was to determine the effect of early or late introduction on the time to successful establishment of full enteral feeding and on adverse outcomes including NEC. Methods: Babies with birth weight below 10th centile and gestation below 34+6 weeks, born after abnormal antenatal Dopplers, were randomised between 20 and 48 h to either early (24–48 h) or late (120–144 h) introduction of milk feeds. Written, informed parental consent was obtained. Babies with major congenital anomaly, in utero transfusion, multiorgan failure or need for inotropes were excluded. Feed volumes and rate of increase were standardised and were the same for both groups. Daily feed logs were kept. Results: 404 babies were randomised from 54 hospitals in the UK and Ireland (202 in each group) between 1 April 2006 and 31 May 2009. There were no important differences between groups at randomisation. Outcome data have been received on 372 babies to date and are presented below. Conclusion: Growth-restricted preterm infants born after absent or reversed end-diastolic flow in the umbilical artery who are fed from the second day after birth achieve full feeds earlier than those commencing feeds on day 6. No difference has been seen to date in the incidence of NEC or sepsis.